2020
DOI: 10.1002/cncr.33202
|View full text |Cite
|
Sign up to set email alerts
|

Cancer patients' experiences with medicinal cannabis–related care

Abstract: BACKGROUND: Little is known about medical cannabis (MC)-related care for patients with cancer using MC. Methods: Semistructured telephone interviews were conducted in a convenience sample of individuals (n = 24) with physician-confirmed oncologic diagnoses and state/district authorization to use MC

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
45
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 40 publications
(51 citation statements)
references
References 18 publications
6
45
0
Order By: Relevance
“…Similar to our findings, other studies have also identified anxiety and sleep problems as primary symptoms managed by cancer patients using medicinal cannabis [ 25 , 26 , 27 , 28 ].…”
Section: Discussionsupporting
confidence: 92%
“…Similar to our findings, other studies have also identified anxiety and sleep problems as primary symptoms managed by cancer patients using medicinal cannabis [ 25 , 26 , 27 , 28 ].…”
Section: Discussionsupporting
confidence: 92%
“…Approximately half of individuals with cancer noted that they had spoken with their doctor. We have no evidence as to the amount of education that individuals might have received in setting of these conversations, but others have noted that little advice is given by providers when Cannabis use is revealed [20]. Available data suggest that much patient education on Cannabis comes from outside of the medical community [20].…”
Section: Plos Onementioning
confidence: 96%
“…This report by Braun et al 3 focuses on patients using cannabis as part of their cancer treatment. The authors conducted telephone interviews to survey participants across the country (United States) about their cannabis use and about interactions between the patients and their medical staff with respect to this use.…”
mentioning
confidence: 99%